Geochemistry of sediments and volcanic ash from Southcentral Alaska (IEDA: EarthChem Library)
The subarctic Pacific Ocean and Bering Sea comprise the second-largest high nitrate, low chlorophyll region in the world, where primary production is limited by the availability of iron (Fe). To estimate the potential impact of different terrestrial aerosol Fe sources on marine ecosystems, we performed a suite of laboratory assessments following established protocols, including: 1) leaching with Milli-Q water, 2) sequential extractions, 3) complete acid digestions, 4) X-ray diffraction, and 5) grain size analysis. Measurements were performed on 20 fine-grained (<5 μm) glacier-derived sediments from Alaska and the Yukon, 2 fresh, never-wetted volcanic ashes (Redoubt 2009 and Pavlof 2016), and 6 weathered ashes (Redoubt and Augustine) which span the past ~8700 years. We compared results to published data on Asian desert-derived sediments, finding that the glacier-derived sediments have five times higher easily-reducible Fe (median 2.3 ± 0.6 wt. %) than desert-derived samples (0.49 ± 0.1 wt. %) and fourteen times higher easily-reducible Fe than fresh ash (0.16 ± 0.1 wt. %). In addition, fractional Fe solubility was higher in glacial sediment (median cumulative 0.31 ± 0.11% FeS) than volcanic ash (0.04 ± 0.02 % FeS). Glacial sediments also contained higher concentrations of bioactive metals including Co, Ni, Cu, Zn, Mo, Cd, and Pb. Inferred Fe availability increased with sample age, pointing to the ability of environmental weathering processes to change Fe geochemistry.